ANALISIS KEPEMIMPINAN KEWIRAUSAHAAN PADA STARTUP BERBASIS METAVERSE DI INDONESIA - Nurillah Jamil Achmawati Novel; Pratami Wulan Tresna (JURNAL LENTERA BISNIS, 2024)
This research focuses on analyzing the dimensions of entrepreneurial leadership in metaverse-based startups in Indonesia. The aim of the research is to determine the implementation of entrepreneurial leadership in startups, using eight dimensions of leadership according to Bagheri & Harrison (2020): Framing Challenges, Absorbing Uncertainty, Underwriting, Building Commitment, Defining Gravity, Opportunity Identification and Exploitation, Orientation Toward Learning, and Creative Collective Self-Efficacy. The research method uses a mixed approach, with quantitative data collection through questionnaires filled out by 156 respondents from the Bandung Startup community, and qualitative data through in-depth interviews with 11 informants. The research results show that the entrepreneurial leadership dimension in metaverse startups received very high ratings, with an average score above 4.3 on a 1-5 Likert scale. The main findings from interviews indicate that metaverse-based startups are generally full-time remote, flexible, and oriented towards completing work targets. Additionally, opportunities in the metaverse industry to generate revenue and grow businesses are still vast, requiring constant innovation from leaders. In conclusion, entrepreneurial leadership plays an important role in managing the dynamics of metaverse-based startups, accompanied by high adaptation and innovation to achieve optimal performance in a rapidly developing ecosystem.